Determining the Surface Tension of a Liquid And the Drop Comparison Method - Mukti Ali; Muh Syihab Ikbal; Jusman (Pendidikan Fisika UIN Alauddin Makassar, 2023)
The purpose of this study was to find out how to determine the surface tension of a liquid using the drop method followed by a comparison method. The method used in this research is the experimental method. The data obtained from the experiment is in the form of quantitative data. The experimental method uses a drip burette, beaker and digital balance as a tool to determine surface tension using the drop method followed by a comparison method. The drip method is followed by a comparison method reviewed by looking at the ratio of the number of drops of liquid to the rate of volume reduction at the specified burette. The liquid substances compared in this study are distilled water and glycerin. The two liquids are put into the drip burette and then the number of drops is counted at the same (set) volume reduction rate. The analysis used is to determine the density of the two substances (aquades and water) and then proceed with analysis to calculate the surface tension. From the results of the research that has been done, the results of the percent difference (% difference) for the surface tension of water and glycerin are 1% and 1.96% respectively, with absolute error values ∆aquades = 1.83 dyne/cm and ∆glycerin = 1.68 dyne/cm with a relative error of 2% each